IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN KEMAMPUAN IDENTIFIKASI UNSUR INTRINSIK CERITA PESERTA DIDIK KELAS V-C SDN PAKIS V SURABAYA - Assa Roseana; Anik Kirana; Ahmad Khoirussyifa Amrullah (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2024)
The aim of this research was to improve students' ability to identify the intrinsic elements of stories in Indonesian language subjects for class V-C at SDN Pakis V Surabaya. This research is a type of classroom action research (PTK) carried out in two cycles. The research subjects were 30 students in class V-C at SDN Pakis V Surabaya 2024/2025. This research consisted of the independent variable (X) being the implementation of the CRT approach and the dependent variable (Y) being the ability to identify the intrinsic story elements of students in class V-C at SDN Pakis V Surabaya. Data collection techniques use observation and tests. The data was analyzed descriptively quantitatively based on the percentage of learning outcomes in pre-cycle, cycle I and cycle II. After conducting research, the results were that the application of the culturally responsive teaching (CRT) approach could improve Indonesian language learning outcomes, especially the intrinsic story element material. Before the action was taken, only 23% of students were able to identify the intrinsic elements of the story, in cycle I this increased to 63% who were able to identify the intrinsic elements of the story, and in cycle II to 87% who were able to identify the intrinsic elements of the story. This research shows that students in class V-C at SDN Pakis V Surabaya are able to achieve better learning outcomes in Indonesian with intrinsic story element material if they use a culturally responsive teaching (CRT) approach.